Önde Gelen Iktisat Doktora Programlarında Temel Makro Iktisat Eğitimi - Graduate Macroeconomics Education in Leading PH.D Programs in Economics - Ahmet Faruk Aysan; Yavuz Selim Hacihasanoglu; Gazi Ishak Kara; Amac Suner (Turkish Economic Association, 2006)
– This paper analyzes the current state of research in macroeconomics in the light of first year macroeconomics courses offered in the 16 leading Ph.D programs. Our investigation confirms that methodological and ideological differences of 1970s and 80s are about to disappear as methodological gap between macroeconomics and microeconomics is narrowing. Moreover, while use of mathematics in macroeconomics is increasing, applied mathematics gains more importance than theoretical mathematics. This paper also shows that, in the first year of Ph.D. programs, lectures in macroeconomics are designed to teach basic techniques and methods while the topics like the imperfection based models, monetary and fiscal policies, welfare implications of these policies and the role of institutions in economy are left to the following years.
Keywords: A23; B22; 330; Graduate macroeconomics teaching; use of mathematics in macroeconomics; difference between undergraduate and graduate education in macroeconomics; ideology and methodology in macroeconomics